Shanghai Preconception Cohort (SPCC) for the association of periconceptional parental key nutritional factors with health outcomes of children with congenital heart disease: a cohort profile - Yuhuan Liu; Lei Zhang; Qing Liu; Hong Zhu; Ying Wang; Hong Huang; Min Jiang; Yi Zhang; Xiaojing Ma; Dingmei Wang; Yuang Jiang; Ying Ye; et al. (BMJ Open)
Purpose The Shanghai Preconception Cohort (SPCC) was initially established to investigate the associations of parental periconceptional nutritional factors with congenital heart disease (CHD) but has further analysed child growth and development and paediatric diseases.Participants Preparing-for-pregnancy couples who presented at Shanghai preconception examination clinics and early-pregnancy women before 14 gestational weeks were enrolled to comprise the periconceptional baseline study population. General characteristics, routine clinical data and consumption of diet supplements, such as folic acid and multivitamins, were collected. Blood samples were obtained at preconception and early, middle and late gestations using standard procedures. Multiple nutritional factors, including folate, homocysteine, vitamin A, vitamin D, vitamin E and metals, in the blood samples of participants selected using a case–control design were examined. Genomic DNA was extracted.Findings to date The baseline population included 8045 preconception couples, 3054 single women and 15 615 early-pregnancy women. Data from 12 402 births were collected, and follow-up of the cohort for other outcomes is ongoing. Currently, 151 cases of CHD were identified after birth. The pilot analysis in a small subgroup showed that approximately 20.0% of preconception women and 44.9% of early-pregnancy women had red blood cell (RBC) folate levels that met the international recommendation for preventing neural tube defects.Future plans Once a sufficient number of CHD cases are achieved, we will investigate the quantitative association of preconception RBC folate levels with CHD using a nested case–control design. The SPCC will be followed up for 18 years to investigate extensive outcomes of growth, development, obesity, and common and rare diseases during childhood and adolescence according to our plan. Blood nutritional factors will be examined in participants selected for specific aims. The SPCC will also allow for prospective cohort studies on extensive research questions.Trial registration number NCT 02737644